INTERNATIONAL INVESTMENT COOPERATION OF THE VISEGRAD FOUR COUNTRIES - FLISSAK, Kostiantyn (Scientific journal «World of Finance», 2021)
Introduction. One of the challenges of the globalized world economic system to national economies is the need to optimize their participation in the international division of labour. In this regard, increases the importance of the investment segment of foreign economic activity in achieving economic growth in competitive conditions with the priority of providing national economic interests .The purpose of the article is to review the investment relations of the Visegrad four countries in dynamics, to determine their investment priorities in attracting foreign direct investment in the national economy and in making direct capital investments abroad, to summarize their practice of supporting investment in the country and abroad, to draw attention to the possibilities of their adaptation to the Ukrainian practice of foreign economic activity.Results. There are considered the financial component of foreign economic activity of the Visegrad four countries in the investment segment, the dynamics of bilateral investment flows, and the features and priorities of investment cooperation between the countries in foreign markets. There is drawn attention to the system of providing state support for investing within countries and abroad in the interests of the national economy.Conclusions. The dynamics of the investment segment of the Visegrad four countries in foreign economic activity demonstrates the priority of countries in expanding their investment presence in foreign markets. At the same time, the national interests of each of the states, taking into account EU membership, are different, which determines the presence of peculiarities in the formation and implementation of the investment policy of each of the countries. The implementation of the priority of expanding the investment presence in foreign markets and effectively attracting FDI to the national economy increases, despite the market status, role and impact of state regulation of these processes. State assistance is implemented by appropriate regulatory support for investment activities, the use of a wide range of financial and institutional support for investment cooperation, the creation of a network of structures for implementing investment policy, taking into account the specifics of countries and in the context of promoting national economic interests.